Recursos hídricos e desenvolvimento sustentável (escala de necessidades humanas e manejo ambiental integrado) ) (GEOgraphia, 2009)
O presente artigo aborda  a questão dos  recursos  hídricos  e a sustentabilidade do desenvolvimento para  discussão de subsídios para melhoria do uso da água, - elemento essencial à vida.  -,  no âmbito de bacias e sub-bacias hidrográficas. Qualquer ação ou política desenvolvida para tratar dos recursos hídricos, só colherão bons  resultados se considerarem as bacias de drenagem como unidades de planejamento e gestão ambiental. A título de exemplo, considerou-se o Plano de Recursos Hídricos do Estado do Ceará, concebendo-o como um estudo de caso da Sub-bacia Metropolitana do Pacoti - Ceará. AbstractThe present work  approaches  the hydrological  resources within  the sustainable development  realm,  taking  into account  the  uneven  resource  distribution  in Semi-Arid regions  such  as  the Northeastem  Brazil  and  the Pacoti  river  basin  in  the  State of  Ceará. Although obvious, the water resources are essential  to life. Based on this principie the  idea of sustainable development  is  fully discussed  on  a  local  and global  basis,  so that  to emphasize how  low  are the human  and  social development indexes  related  to  local  inhabitants. A poor State  in  a poor  Region  of  a developing country,  such  as Brazil, shouldn't  operate without local political  bias. Despite the local  improvement  translated  into a more active participation of  locals,  some  rural  projects  are  producing better  results  to  the  rural  people.  Planning  the years ahead seems to be the only way to provide a better life to future generation.